Structuring Islamic financial literacy construct to measure Islamic banking products adoption in Uganda: content validation of the survey instrument - Kaweesa, Yusuf; Rosman, Romzie (Economic and Social Research Institute, 2025)
Islamic banking in Uganda was introduced recently in 2016. However, Islamic microfinance Institutions started operations immediately as they are differently regulated by the Uganda Microfinance Regulatory Authority (UMRA) under the Tier 4 regulatory Act. So, this study aims to structure and conduct content validation of a survey questionnaire of Islamic financial literacy construct for the adoption of Islamic banking products among Muslims in Uganda. Methodologically, this study was executed in five stages. Firstly, the content validation form was prepared detailing the items to be validated and their sources. Secondly, a review panel of experts was selected based on their expertise in Islamic banking adoption and Islamic financial literacy, and 6 experts were considered. Then an online content validation form with clear instructions was sent to experts to critically review the domains and items before scoring them to improve relevance. The results showed that an S-CVI score of 0.864 was attained by the tool and thus relevant to be used for the study. The CVI for Islamic financial literacy was between 0.83-1, and thus, all items were relevant to assess the Islamic financial literacy concept of the Muslims in Uganda. Thus, this tool can be a reference for researchers who intend to conduct research on Islamic financial literacy and other factors of Islamic banking adoption in jurisdictions that have just embraced the Islamic financial system